Interaction of a spatial soliton on an interface between two nonlinear media - Mat Din, Mohd Azid; Ahmad Kamely, Aizuddin; Umarov, Bakhram A.; Mohd Busul Aklan, Nor Amirah (2018)
Spatial solitons are the solutions of nonlinear partial differential equations describing the propagation of optical beams in Kerr type nonlinear medium. This paper studies the scattering of a spatial solitons of the Cubic-Quintic Nonlinear Schrödinger Equation (C-Q NLSE) on an interface between two nonlinear media. The scattering process will be investigated by variational approximation method and by direct numerical solution of C-Q NLSE. This variational approximation method has been used to analyse the dynamic of the width and center of mass position of a soliton during the scattering process. Meanwhile, a direct numerical simulation of C-Q NLSE is run to check the accuracy of the approximation by using the same range of parameters and initial condition. The results for direct numerical simulation of CQNLSE for soliton parameters are quite similar with the variational equation. The studies showed that soliton can be reflected by or transmitted through the interface, also the nonlinear surface wave can be formed depending on the parameters of interface and initial soliton.